The Akhlak Education of Ibn Miskawaih and Its Implementation in the UNIDA Gontor Environment - Fitra Awalia Rahmawati (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
One of the objectives of moral education in this era is to overcome various problems in education and describe the meaning and objectives of education according to the Law of the National Education System. This research attempts to describe the akhlak education of Ibnu Miskawaih, and its implementation in Islamic education at Darussalam University (UNIDA) Gontor. The method used in this research is a qualitative method with a descriptive case study approach. Research data were collected through documents in the form of books and journals that discussed the moral education of Ibnu Miskawaih and his moral philosophy, field observations related to the implementation of Ibn Miskawaih's moral education in the educational environment at UNIDA Gontor, and interviews with lecturers and students regarding academic and non-academic activities. Relevant to the thought of Ibn Miskawaih. This research is expected to be a reference in viewing the implementation of Islamic education by a figure in an institution or educational institution